Entrepreneurship and crisis management: The experiences of small businesses during the London 2011 riots. (May 2016) - Doern, Rachel
This article examines the impact of a crisis on small firms. Taking a phenomenological research approach, qualitative interviews were conducted to capture the experiences of small businesses directly affected by looting, vandalism and/or arson in the London 2011 riots. This study adds to the literature on crisis management by highlighting the different types of losses encountered by small businesses following a crisis and the role individual owner–managers, businesses and the wider community play in enhancing or minimizing losses. A model is developed to capture those factors that influence which small businesses were vulnerable or resilient to the riots.